Drexel dragonThe Math ForumDonate to the Math Forum

Ask Dr. Math - Questions and Answers from our Archives
_____________________________________________
Associated Topics || Dr. Math Home || Search Dr. Math
_____________________________________________

Resultant of Two Polynomials


Date: 09/13/2001 at 08:45:50
From: Lyubomir Ahtarov
Subject: Abstract algebra

Can you give me an example of how to find the resultant of two 
polynomials?


Date: 09/13/2001 at 14:10:45
From: Doctor Rob
Subject: Re: Abstract algebra

Thanks for writing to Ask Dr. Math, Lyubomir.

There are several ways to compute the resultant of two polynomials

           m                     m
   f(x) = SUM a(i)*x^i = a(m)*PRODUCT (x-c(i)),
          i=0                   i=1

           n                     n
   g(x) = SUM b(j)*x^j = b(n)*PRODUCT (x-d(j)).
          j=0                   j=1

1. Use the definition:

                             n       m
   R(f,g) = a(m)^n*b(n)^m*PRODUCT PRODUCT (c(i)-d(j)),
                            j=1     i=1

                      m
          = a(m)^n*PRODUCT g(c(i)),
                     i=1

                                 n
          = (-1)^(m*n)*b(n)^m*PRODUCT f(d(j)).
                                j=1

You don't need to know the roots c(i) or d(j) explicitly. Just
substitute them symbolically into one of the above products, expand 
the result, and simplify using the facts that f(c(i)) = 0 and 
g(d(j)) = 0.

2. Use the (m+n)-by-(m+n) Sylvester determinant:

            |a(n) a(n-1)  ...   ...   a(0)   0    0   ...   0  |
            | 0    a(n)  a(n-1) ...   ...   a(0)  0   ...   0  |
            |...   ...    ...   ...   ...   ...  ...  ...  ... |
   R(f,g) = | 0    ...     0    a(n) a(n-1) ...  ...  a(1) a(0)| (mth 
            |b(m) b(m-1)  ...   ...   b(0)   0    0   ...   0  |  row)
            | 0    b(m)  b(m-1) ...   ...   b(0)  0   ...   0  |
            |...   ...    ...   ...   ...   ...  ...  ...  ... |
            | 0    ...     0    b(m) b(m-1) ...  ...  b(1) b(0)|

3. Use the following recursions to reduce the degrees of the
arguments of the resultant until it can be directly evaluated.
Here k is any constant.

   a. R(f,g) = (-1)^(m*n)*R(g,f),
   b. R(f1*f2,g) = R(f1,g)*R(f2,g),
   c. R(f,g1*g2) = R(f,g1)*R(f,g2),
   d. R(f,k*g) = k^m*R(f,g),
   e. If k*g(x) = q(x)*f(x) + r(x), where p = degree(r) < m,
      then R(f,k*g) = a(m)^(n-p)*R(f,r).
   f. R(f,k) = k^m.

Examples of all three methods for the two polynomials

   f(x) = 2*x^2 - 5*x + 1,           m = 2,
   g(x) = 3*x^3 - 2*x^2 + 2*x + 1,   n = 3,

follow.

1. Use the second product formula for the resultant:

   R(f,g) = a(2)^3*g(c(1))*g(c(2)),
          = 2^3*(3*c(1)^3-2*c(1)^2+2*c(1)+1)*
              (3*c(2)^3-2*c(2)^2+2*c(2)+1),
          = 72*c(1)^3*c(2)^3 - 48*c(1)^3*c(2)^2 + 48*c(1)^3*c(2) +
              24*c(1)^3 - 48*c(1)^2*c(2)^3 + 32*c(1)^2*c(2)^2 -
              32*c(1)^2*c(2) - 16*c(1)^2 + 48*c(1)*c(2)^3 -
              32*c(1)*c(2)^2 + 32*c(1)*c(2) + 16*c(1) + 24*c(2)^3 -
              16*c(2)^2 + 16*c(2) + 8,
          = 72*[c(1)*c(2)]^3 - 48*[c(1)+c(2)]*[c(1)*c(2)]^2 -
              64*[c(1)*c(2)]^2 + 48*[c(1)+c(2)]^2*[c(1)*c(2)] -
              104*[c(1)+c(2)]*[c(1)*c(2)] + 64*[c(1)*c(2)] +
              24*[c(1)+c(2)]^3 - 16*[c(1)+c(2)]^2 + 16*[c(1)+c(2)] + 8

Now use c(1)*c(2) = -a(1)/a(2) = 1/2, c(1) + c(2) = a(0)/a(2) = 5/2:

   R(f,g) = 72*(1/2)^3 - 48*(5/2)*(1/2)^2 - 64*(1/2)^2 +
              48*(5/2)^2*(1/2) - 104*(5/2)*(1/2) + 64*(1/2) +
              24*(5/2)^3 - 16*(5/2)^2 + 16*(5/2) + 8,
          = 9 - 30 - 16 + 150 - 130 + 32 + 375 - 100 + 40 + 8,
          = 338


            |2 -5  1  0  0|   |2  -5    1    0   0|
            |0  2 -5  1  0|   |0   2   -5    1   0|
2. R(f,g) = |0  0  2 -5  1| = |0   0    2   -5   1|,
            |3 -2  2  1  0|   |0 11/2  1/2   1   0|
            |0  3 -2  2  1|   |0   0  11/2  1/2  1|


            |2 -5   1    0    0 |
            |0  2  -5    1    0 |     |  2   -5    1 |
          = |0  0   2   -5    1 | = 4*|57/4 -7/4   0 |,
            |0  0 57/4 -7/4   0 |     |  0  57/4 -7/4|
            |0  0   0  57/4 -7/4|

              |  0    0  1352/3249|
          = 4*|57/4 -7/4     0    |  = 4*(57/4)^2*(1352/3249),
              |  0  57/4   -7/4   |

          = 338.

3. g(x) = f(x)*(6*x+11)/4 + (57*x-7)/4, so r(x) = (57*x-7)/4, p = 1.

   R(f,g) = 2^2*R(f,r) = 4*R(f,r),
          = 4*[(-1)^(2*1)*R(r,f)],
          = 4*R(r,f).

f(x) = (8*x/57-1084/3249)*r(x) + 1352/3249, so r'(x) = 1352/3249,
p' = 0.

   R(f,g) = 4*R(r,f),
          = 4*[(57/4)^2*R(r,r')],
          = (57^2/4)*R(r,r'),
          = (57^2/4)*1352/3249 = 338.

I hope this is what you were seeking.  If not, write again.
          
- Doctor Rob, The Math Forum
  http://mathforum.org/dr.math/   
    
Associated Topics:
College Modern Algebra

Search the Dr. Math Library:


Find items containing (put spaces between keywords):
 
Click only once for faster results:

[ Choose "whole words" when searching for a word like age.]

all keywords, in any order at least one, that exact phrase
parts of words whole words

Submit your own question to Dr. Math

[Privacy Policy] [Terms of Use]

_____________________________________
Math Forum Home || Math Library || Quick Reference || Math Forum Search
_____________________________________

Ask Dr. MathTM
© 1994-2013 The Math Forum
http://mathforum.org/dr.math/